Lipidomic changes of cerebral cortex in aldehyde dehydrogenase-2 knock-in heterozygote mice after chronic alcohol exposure - Xiao, Li; Xiang, Jin; Liu, Xinyu; Yang, Lin; Wei, Ying; Fang, Shiyong; Li, Jing; Ye, Yi (Frontiers in Molecular Neuroscience, 2023)
Introduction Alcohol is the main legal drug in the world, and excessive consumption of alcohol seriously damages the morphological structure and function of various organs. The insufficiency of an essential enzyme in ethanol metabolism, aldehyde dehydrogenase-2 (ALDH2), will aggravate the alcohol-induced brain injury. The effect of ALDH2 after chronic alcohol exposure on global lipid profiling of the brain remains unclear. Methods In this study, ALDH2*2 knock-in mice were fed the Lieber-DeCarli liquid diet containing ethanol for 8 weeks. Blood alcohol and acetaldehyde levels were examined, and the mice were tested through novel object recognition and the Y-maze test to evaluate cognitive impairment toward the end of the study. The lipidome profiling of cerebral cortex samples was investigated using a lipidomics method based on ultra-high performance liquid tandem chromatography quadrupole time of flight mass spectrometry (UHPLC-QTOFMS). Results and Discussion Compared with similarly treated wild-type (WT) mice, ALDH2*2 mice exhibited poor cognitive performance, though the result did not achieve statistical significance. The lipidomics results indicated that 74 differential lipid species were selected in WT mice, of which 57 species were up-regulated, and 17 were down-regulated. Moreover, 99 differential lipids were identified in ALDH2*2 mice, of which 73 were up-regulated, and 26 were down-regulated. For ALDH2*2 mice, the number of changed significantly glycerophospholipids (GPs) subtypes was lower than that of WT mice. Interestingly, compared with WT mice, a lower proportion of polyunsaturated fatty acids (PUFAs) was found in ALDH2*2 mice. Collectively, the results provide clear evidence for a lipidomic signature of marked changes in the cerebral cortex of ALDH2*2 mice after chronic alcohol exposure. Highlights • The cerebral cortex of heterozygous ALDH2*2 mice showed more significant changes in lipidome profiles after chronic alcohol exposure than wild-type mice. • Most lipids were significantly up-regulated in both groups of mice, whereas the increase in TAG was restricted to WT mice. • For ALDH2*2 mice, GPs substances changed significantly, and SHexCer and SM subclasses in sphingolipids also deserved attention.